2003
DOI: 10.1051/0004-6361:20030892
|View full text |Cite
|
Sign up to set email alerts
|

Inter-network magnetic fields observed with sub-arcsec resolution

Abstract: Abstract. We analyze a time sequence of Inter-Network (IN) magnetograms observed at the solar disk center. Speckle reconstruction techniques provide a good spatial resolution (0. 5 cutoff frequency) yet maintaining a fair sensitivity (some 20 G). Patches with signal above noise cover 60% of the observed area, most of which corresponds to intergranular lanes. The large surface covered by signal renders a mean unsigned magnetic flux density between 17 G and 21 G (1 G ≡ 1 Mx cm −2 ). The difference depends on the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
62
2
9

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 98 publications
(81 citation statements)
references
References 48 publications
7
62
2
9
Order By: Relevance
“…Previous studies of very quiet regions reported a polarity balance, even with smaller observed areas (e.g. Lites 2002;Domínguez Cerdeña et al 2003;Martínez González et al 2008c). This imbalance occurs for all signals, hence it cannot be a result of unipolar network patches or a unipolar weak component previously undetected.…”
Section: One Magnetic Structure Embedded In a Field-free Atmospherementioning
confidence: 66%
See 1 more Smart Citation
“…Previous studies of very quiet regions reported a polarity balance, even with smaller observed areas (e.g. Lites 2002;Domínguez Cerdeña et al 2003;Martínez González et al 2008c). This imbalance occurs for all signals, hence it cannot be a result of unipolar network patches or a unipolar weak component previously undetected.…”
Section: One Magnetic Structure Embedded In a Field-free Atmospherementioning
confidence: 66%
“…Khomenko et al 2003;Martínez González et al 2008c), other works used visible lines and derived kG fields (e.g. Socas-Navarro & Sánchez Almeida 2002;Domínguez Cerdeña et al 2003). Later, the Hinode satellite provided spectro-polarimetric data in the visible with improved spatial resolution.…”
Section: Introductionmentioning
confidence: 99%
“…IR spectra at 1.56 μm allow us to disentangle most of the ambiguities because the field strength can be inferred from the splitting of the polarization, or in some cases, even the intensity components of the spectral line for magnetic fields above around 400 G (Beck 2006;Beck et al 2007). It is thus unsurprising that studies before HINODE using solely VIS lines (Sánchez Almeida & Lites 2000;Domínguez Cerdeña et al 2003;Socas-Navarro & Sánchez Almeida 2003; or IR lines (Lin 1995;Khomenko et al 2003; Article published by EDP Sciences Martínez González et al 2006a;Domínguez Cerdeña et al 2006a) did not agree especially about the intrinsic field strength: the VIS observations indicated a significant fraction of strong kG fields, whereas the IR was dominated by weaker hG fields.…”
Section: Introductionmentioning
confidence: 99%
“…When averaged over the 30% of the FOV that we study, the mean unsigned flux density turns out to be 11 G in the visible, and 6 G in the IR. Due to the complexity of the IN magnetic fields, the observed unsigned flux is expected to increase with increasing angular resolution (see, e.g., Sánchez Domínguez Cerdeña et al 2003b). The fact that the IR, with higher resolution, has lower unsigned flux, seems to indicate that this is a true solar effect.…”
Section: Resultsmentioning
confidence: 99%